Relationship between Glutamate Dysfunction and Symptoms and Cognitive Function in Psychosis - Merritt, Kate; Mcguire, Philip; Egerton, Alice (Frontiers in Psychiatry, 2013)
The glutamate hypothesis of schizophrenia, proposed over two decades ago, originated following the observation that administration of drugs that block NMDA glutamate receptors, such as ketamine, could induce schizophrenia–like symptoms. Since then, this hypothesis has been extended to describe how glutamate abnormalities may disturb brain function and underpin psychotic symptoms and cognitive impairments. The glutamatergic system is now a major focus for the development of new compounds in schizophrenia. Relationships between regional brain glutamate function and symptom severity can be investigated using proton magnetic resonance spectroscopy (1H-MRS) to estimate levels of glutamatergic metabolites in vivo. Here we briefly review the 1H-MRS studies that have explored relationships between glutamatergic metabolites, symptoms and cognitive function in clinical samples. While some of these studies suggest that more severe symptoms may be associated with elevated glutamatergic function in the anterior cingulate, studies in larger patient samples selected on the basis of symptom severity are required.